A transcriptional cross-talk between RhoA and c-Myc inhibits the RhoA/Rock-dependent cytoskeleton - Bustelo, Xosé R (Landes Bioscience, 2010)
The GTPase RhoA and the transcriptional factor c-Myc are closely intertwined in cancer cells. Although this cross-talk results in potent synergistic effects that favor the transformed phenotype of cancer cells, recent results from our laboratory indicate that c-Myc also participates in a negative feed-back loop that blocks specific RhoA signaling branches connected to the induction of stress fibers, focal adhesions and actomyosin contractility. Using microarray analysis, we have unveiled a RhoA/c-Myc-dependent gene signature in charge of this negative cross-talk. This signature is composed of upregulated and repressed transcripts encoding cytoskeletal modulators located downstream of both RhoA and Rock. Our results also indicate that this negative feed-back loop modifies the invasion and adhesion properties of RhoA-transformed cells, suggesting that it may be important to ensure fluid cytoskeletal dynamics of cancer cells. Preliminary data indicate that c-Myc may also use a different transcriptional program to interfere with the RhoA/Rock-dependent cytoskeletal branch in non-transformed cells.